PEMANFAATAN TEKNOLOGI INFORMASI DALAM RANGKA MEMBERANTAS TINDAK PIDANA KORUPSI SECARA ELEKTRONIK - Edi Nugroho (Jurnal Dinamika Hukum, 2014)
Eradication of corruption in repressive/enforcement/penal would be more effective if accompanied by efforts in preventive/precautionary/non penal. One of the sources of corruption that resulted in losses to the state and the country’s economy is in terms of government procurement of goods and services. Efforts to prevent corruption in the procurement of government goods and services, as well as efforts to create good governance and free from corruption, collusion and nepotism in providing services to the public, is to utilize information and communication technology, in the form of e-government and e-procurement, as part of efforts to eradicate corruption in Indonesia.Key words: corruption, prevention, eradication, e-government, e-procurement.